Zelda and Ivy - Kvasnosky, Laura McGee (Somerville, Mass Candlewick Press, 2010)
After fox sisters Zelda and Ivy and their best friend Eugene watch the new Secret Agent Fox movie, they are inspired to do some detective work then practice their new skills when rain threatens their campout plans
Keywords: Camping -- Fiction; Detectives -- Fiction; Foxes -- Fiction; Sisters -- Fiction